TATALAKSANA MIOMA UTERI MANAGEMENT OF UTERINE MYOMA - Primadella Fegita (Nusantara Hasana Journal, 2024)
Background: Uterine myoma is the most benign tumor of the genital organs in women of reproductive age, causing morbidity and impaired quality of life for women. Risk factors associated with uterine myoma include age, race, heredity, sex hormones, obesity, lifestyle (diet, caffeine, and alcohol consumption, smoking, physical activity and stress), environment and other influences such as hypertension and infection. Uterine myoma is known as uterine fibromyoma, uterine leiomyoma, or uterine fibroid. Uterine myoma contains smooth muscle and fibrous tissue. Uterine myoma occurs in 20 - 25% of women of reproductive age. Myomas are rarely discovered before the age of puberty, as they are strongly influenced by reproductive hormones and only manifest during reproductive age. Although it rarely causes mortality, the morbidity caused by uterine myoma is quite high because uterine myoma can cause abdominal pain and abnormal bleeding, and is thought to cause low fertility. This case report will report a case of a 44-year-old female patient diagnosed with P0H0 + Suspect Uterine Myoma dd Adenomyosis + History of Laparotomy. The patient is finally treated by performing a total hysterectomy.